Pengaruh Program Latihan Pliometrik Terhadap Peningkatan Power Tungkai pada Atlet Lompat Jauh - Muhammad Jabbar Balya; Agus Gumilar; Ahmad Hamidi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
Leg power is one of the biomotor components that greatly determines the success of long jump athletes, especially in the take-off phase. One of the most widely used training methods to increase leg muscle explosive power is plyometric training, which utilizes the stretch-shortening cycle (SSC) mechanism. However, research on the effectiveness of plyometric training in adolescent long jump athletes in Indonesia remains limited. This study aims to determine the effect of a plyometric training program on increasing leg power in adolescent long jump athletes and to analyze the effect size of the program. The study used a quantitative approach with a One Group Pretest-Posttest Design. The research sample consisted of 10 adolescent long jump athletes selected using a total sampling technique. Leg power was measured using the 30-Second Sit-to-Stand (30s STS) test before and after the plyometric training program. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Paired Samples t-test, and Cohen's d calculation to measure effect size at a significance level of 5%. The results showed: (1) the average pretest score was 49.40, while the average posttest score increased to 54.90, with an average increase of 5.50 points; (2) the normality test showed that the pretest (Sig. = 0.953) and posttest (Sig. = 0.999) data were normally distributed; (3) the Paired Samples t-test showed a significance value of p < 0.001, indicating a significant difference between the pretest and posttest scores; (4) the Cohen's d analysis yielded a value of 2.09, indicating that the plyometric training program had a huge positive effect on increasing athletes' leg power. It can therefore be concluded that the plyometric training program is effective and has a significant effect on increasing leg power in adolescent long jump athletes. Keywords: Effect Size, Plyometric Training, Long Jump, Leg Power, Stretch-Shortening Cycle